Bio‐Inspired Isoalloxazine Redox Moieties for Rechargeable Aqueous Zinc‐Ion Batteries. Issue 8 (23rd March 2020) - Cheng, Liwei; Liang, Yanhong; Zhu, Qiaonan; Yu, Dandan; Chen, Mengxue; Liang, Junfei; Wang, Hua
Abstract: Organic electrode materials hold great potential for fabricating sustainable energy storage systems, however, the development of organic redox‐active moieties for rechargeable aqueous zinc‐ion batteries is still at an early stage. Here, we report a bio‐inspired riboflavin‐based aqueous zinc‐ion battery utilizing an isoalloxazine ring as the redox center for the first time. This battery exhibits a high capacity of 145.5 mAh g −1 at 0.01 A g −1 and a long‐life stability of 3000 cycles at 5 A g −1 . We demonstrate that isoalloxazine moieties are active centers for reversible zinc‐ion storage by using optical and photoelectron spectroscopies as well as theoretical calculations. Through molecule‐structure tailoring of riboflavin, the obtained alloxazine and lumazine molecules exhibit much higher theoretical capacities of 250.3 and 326.6 mAh g −1, respectively. Our work offers an effective redox‐active moiety for aqueous zinc batteries and will enrich the valuable material pool for electrode design. Abstract : A bio‐inspired isoalloxazine redox moiety is demonstrated to be capable of reversible zinc‐ion storage through a two‐electron transfer process. When used in aqueous zinc‐ion batteries, it exhibits promising specific capacity and adjustable electrochemical property by molecular structure tailoring. It presents a new category for sustainable zinc‐organic batteries.